The complete chloroplast genome sequence of the medicinal plant Persicaria filiformis - Kun Zhang; Zhihui Gao; Zhiping Han; Xiaofei Shan (Mitochondrial DNA. Part B. Resources, 2021)
Persicaria filiformis, known as a traditional Chinese herbal medicine, is a perennial plant of Polygonaceae wildly distributed in China. The complete chloroplast (cp) genome of P. filiformis was assembled and analyzed in this study. The length of the circular genome is 159,741 bp, with a rich GC content of 41.3%. The cp genome structure consists of a large single-copy region (LSC 84,432 bp), a small single-copy region (SSC 13,073 bp) and a pair of inverted repeat regions (IR 31,118 bp). The complete genome encodes 130 genes, including 85 protein-coding genes, 37 tRNA genes and 8 rRNA genes. Phylogenetic analysis indicated that P. filiformis is most related to P. japonica.